Coping strategies of the sandwich generation in the care process: a qualitative study - Pashazade, Hakime; Maarefvand, Masoomeh; Abolfathi Momtaz, Yadollah; Abdi, Kianoush (Springer Nature, 2024)
Objective: The sandwich generation refers to individuals who are simultaneously responsible for caring for their aging parents and their own children. Research shows that the number of sandwich generation caregivers is increasing, and they face significant physical, psychological, social, and economic challenges. Therefore, it is crucial for these caregivers to develop effective coping strategies. This study aimed to identify the coping mechanisms used by sandwich generation caregivers. Methods: In 2022, during the COVID-19 pandemic, we conducted a qualitative study involving semi-structured interviews with 18 sandwich generation caregivers in Tehran, Iran, who were responsible for both elderly parents and their own children. These interviews were conducted either in person or by telephone. Subsequently, the collected data were analyzed using the inductive content analysis method within the MAXQDA software (2018 version). Results: Data analysis revealed three categories of coping strategies: “distancing from the situation”, “self-soothing” (including sub categories of spiritual matters, establishing relationships, emotional outlet, and engaging in favorite activities), and “diversifying responses to needs” (including transferring responsibility to the family members, prioritizing needs for responsiveness, utilizing available community services, mediating to reduce conflict, and remote monitoring of the older adult). Conclusion: Sandwich generation caregivers use various coping strategies, each with different outcomes. This study found that self-care and using social resources can greatly reduce caregiving burdens. Therefore, providing these caregivers with training in problem-solving and self-care skills is recommended to better prepare them for their responsibilities.